Argentinian odonates (dragonflies and damselflies): Current and future distribution and discussion of their conservation - Nava Bolaños, A. (2021)
In terms of conservation, Argentinian odonates have not been assessed using a quantitative approach. One way to achieve this is by modelling their distribution to gather the extent of occurrence. Thus, we modelled the current and future (projected year, 2050) potential distribution of 44 odonate species that occur in Argentina as well as in neighboring countries. Our models of current times indicate a fairly wide distribution for most species but one exception is relevant for conservation purposes: Lestes dichrostigma has less than 30,000 km2 and falls in the ‘Near Threatened’ category according to the IUCN Red List. Another seven species have less than or close to 100,000 km2: Elasmothemis cannacrioides, Erythemis credula,E. paraguayensis, Heteragrion angustipenne, H. inca, Lestes forficula, and Mecistogaster linearis. Future distribution estimates suggest that: a) 12 species will lose or gain around 10%, four species will increase their distribution beyond 10% (up to 2,346%), and 28 species will lose more than 10% (up to 99%). Although current protected areas embrace most odonate species in Argentina, it is still premature to conclude whether this situation will remain in the future given the physiological tolerance and dispersal abilities of the study species among other drivers of distribution.